The Influence of Viral Marketing and Price on Purchasing Decisions Through Customer Trust: Case Study of the Skincare Brand Skintific - Wulandari, Natasya; Arafah, Willy (IJBLE Scientific Publications Community Inc., 2024)
This study aimed to explore the impact of viral marketing, pricing strategies, and consumer trust on purchasing decisions regarding products released by Skintific. The approach utilized in this study was quantitative, with a sample size of 90 respondents who had already made purchases of Scientific products. Analysis conducted using SEM-PLS revealed that both viral marketing and consumer trust in Scientific products positively influenced consumers' willingness to transact, while pricing did not significantly affect purchase decisions. Additionally, it was found that other factors such as gender, age, and duration of consumer engagement with social media also had an impact